Pet Attachment dan Self-Compassion dengan Psychological Well- Being Pada Pemelihara Kucing - Trinanda, Gilang; Indrawati, Erdina (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This research is a quantitative study which aims to determine the relationship between PetAttachment and Self-Compassion with Psychological Well-Being in cat keepers in the Taman BuaranIndah IV complex. The sampling technique in this research used a Voluntary Sampling technique.Participants in this research were 123 people who kept cats in the Taman Buaran Indah IV complex.Data collection in this study used three scales, namely the Psychological Well-Being scale whichhas 21 items with a different power of 0.303 – 0.647 and a reliability of 0.846. This research datawas analyzed using the enter linear regression method and stepwise linear regression using the JASP(Jeffrey's Amazing Statistics Program) version 0.18.3.0. The results of this research show that 1)There is no significant relationship between Pet Attachment and Psychological Well-Being (r = 0.144and p > 0,05); 2) There is a significant relationship between Self-Compassion and PsychologicalWell-Being (r = 0.436 and p < 0,05); 3) There is a significant relationship between Pet Attachmentand Self-Compassion with Psychological Well-Being (R = 0.274 and p < 0,05). This shows that thereis a relationship between Pet Attachment and Self-Compassion with Psychological Well-Beingamong cat keepers in the Taman Buaran Indah IV complex. It is known that the determinantcoefficient of R Square is 0.191. This means that Pet Attachment and Self-Compassion togethercontribute to Psychological Well-Being by 19.1%, thus as much as 80.9% is influenced by factorsnot researched.